(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
The digital era demands significant adaptation in the field of education, including the implementation of digital literacy in the learning process. In the context of Islamic Religious Education (PAI), digital literacy plays an important role in creating relevant and effective learning. However, the implementation of digital literacy still faces various challenges, particularly related to teachers’ readiness in operating and utilizing technology optimally. The rapid development of technology requires changes in both teaching methods and learning materials, prompting teachers and students to possess adequate digital literacy skills. This study aims to identify the problems faced by teachers in utilizing digital literacy in PAI learning, as well as to analyze the efforts that have been made to address these challenges. The research uses a descriptive qualitative method with data collection techniques including observation, in-depth interviews, and documentation. Primary data sources were obtained from the Principal, two PAI teachers, and ten eighth-grade students, while secondary data were collected from supporting documents related to the use of digital literacy. The findings reveal several problems, such as the low competency of teachers in using digital technology, limited supporting infrastructure, and low levels of student digital literacy, especially in terms of device access, application understanding, and critical information filtering. The efforts made include gradual improvement of facilities, teacher training although not yet conducted regularly and the habituation of using digital media in the learning process.